Business Model Transformation in the Creative Economy Era: A Study on Local Culinary Business (Amuntai City, HSU Regency) - Haris Fadillah; Ahmad Firman Hakim (Journal of Business Transformation and Strategy, 2025)
Abstract: This study aims to explore the business model transformation strategies of local culinary entrepreneurs in the creative economy era. Employing a qualitative approach with a case study design, primary data were collected through in-depth interviews and field observations, while secondary data were obtained from relevant documents and reports. Thematic analysis was used to identify patterns and themes from the collected data. The findings reveal that the implementation of digital technologies, innovation based on local culture, and strengthening collaborative networks are key strategies for enhancing competitiveness. Entrepreneurs leverage digital platforms, such as social media and food delivery applications, to expand market reach and improve operational efficiency. Cultural-based innovation, including traditional elements in product offerings, adds significant value and reinforces brand identity. However, challenges such as limited digital literacy, financial constraints, and resistance to change hinder the transformation process. This study concludes that successful business model transformation in the culinary industry requires a balance between technological adoption and cultural preservation. The findings provide theoretical and practical insights, offering a guide for stakeholders in developing sustainable business models in the creative economy sector